Beyond Normative Preaching: How TikTok Reconstructs Local Wisdom-Based Da’wah in the Nahdlatul Ulama Community - Subahri, Bambang; Rachman, Rio Febriannur (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study examines how Islamic education grounded in local wisdom is constructed and disseminated through the TikTok account of NU Lumajang. The research draws on the theoretical perspectives of the mediatization of religion and on Clifford Geertz's concept of religion as a cultural system to explain the interaction among media logic, religious authority, and local cultural values in digital environments. Employing a qualitative netnographic approach, the study investigates the production, circulation, and audience engagement of religious content on social media. Data were collected through the observation and documentation of 87 TikTok videos uploaded throughout 2025, analysis of user interactions in the comment sections, and in-depth interviews with account managers and selected followers to strengthen the interpretation of online findings. The findings reveal that Islamic education on TikTok NU Lumajang is communicated through short, visually engaging videos that integrate normative Islamic teachings with local traditions, cultural symbols, and regional languages. This strategy enables Islamic values to be conveyed in a contextual, inclusive, and accessible manner while reinforcing local cultural identity. The study concludes that TikTok NU Lumajang functions as a digital space where religious authority, local wisdom, and platform logics are continuously negotiated. The article contributes to the growing scholarship on digital religion by demonstrating how Islamic organizations utilize social media not only to disseminate religious teachings but also to preserve and recontextualize local cultural traditions within contemporary digital communication practices.